Oleanolic acid (OA) regulates inflammation and cellular dedifferentiation of chondrocytes via MAPK signaling pathways - Phull, A-R.; Eo, S-H.; Kim, S. J. (Cellular and Molecular Biology, 2017)
Oleanolic acid (OA) is a bioactive triterpenoid in medicinal plants. It possesses various pharmacological properties, including analgesic, anti-inflammatory, and antitumor effects. The effects of OA in chondrocytes, however, are not well characterized. Here, we used rabbit articular chondrocytes as a cellular model to investigate the effects and regulatory mechanisms of OA on dedifferentiation and pro-inflammation. OA promoted dedifferentiation of chondrocytes by inhibiting type II collagen and pro-inflammatory activity by increasing cyclooxygenase-2 (COX-2) expression. Furthermore increased phosphorylation of p38 kinases and down-regulated phosphorylation of ERK was observed. Inhibition of p38 with SB203580 in OA-treated cells rescued the expression of type II collagen and suppressed the expression of COX-2. However, ERK inhibition with PD98059 accelerated the OA-induced inflammatory responses. These results suggest that OA induces loss of type II collagen expression via the p38 pathway and induces inflammation through the p38 and ERK pathways in rabbit articular chondrocytes.